Duloxetine for Postoperative Pain in Orthopedic Surgeries: A Review Article - Alireza Nankali; Maryam Sabouri; Hediye Gholamshahi (Journal of Orthopedic and Spine Trauma)
post-operative pain plays a key role in patients’ satisfaction. Since opioids may cause dependence and have a high abuse rate, non-opioid drugs such as Duloxetine are being investigated for their effect in this matter. Duloxetine is a dual serotonin and norepinephrine reuptake inhibitor (SNRI) which causes a synergism effect and can help manage post operative pain. For this cause, it’s prescribed as 60mg per day. There have been studies in the recent years proving its effectiveness both in total arthroplasty and elective surgeries. The collective data shows that duloxetine can be used for post-operative pain management, and with minimal side effect, it can lower the opioid usage and dependence.